Ramucirumab plus FOLFIRI or irinotecan as second-line treatment for patients with gastroesophageal adenocarcinoma: a review and meta-analysis of an emerging option - Park, Haeseong; Klempner, Samuel J.; Chao, Joseph; Wainberg, Zev A.; Lukanowski, Mariusz; Chenji, Suresh; Bourke, Shannon; Chatterjee, Anindya; Lorenzen, Sylvie (Frontiers in Oncology, 2024)
The aim of this study was to provide a review of the clinical evidence for use of ramucirumab (RAM) plus folinic acid (leucovorin), fluorouracil (5-FU), and irinotecan (FOLFIRI) or irinotecan as second-line treatment in gastroesophageal adenocarcinoma (GEA). A systematic and comprehensive search of PubMed was performed to identify phase 2 clinical trials or retrospective studies using RAM plus FOLFIRI or irinotecan in GEA, including abstracts from major congresses, in addition to published manuscripts. An aggregated review and meta-analysis was performed to assess the effectiveness (overall response rate [ORR] as primary outcome) and safety data of RAM plus FOLFIRI or irinotecan. ORR for each study was calculated with 95% confidence interval estimated from normal approximation. To generate the combined ORR with 95% confidence interval, random-effects meta-analysis was conducted to synthesize response data from available studies. Six studies were identified with non-overlapping populations, 3 phase 2 clinical trials and 3 retrospective studies. Across these studies the ORR ranged from 22% to 38%, and pooled ORR was 25.4%. Two of the 3 studies reported better ORR in patients pretreated with taxanes followed by RAM plus FOLFIRI. Treatment with RAM plus FOLFIRI or irinotecan was well tolerated. Neutropenia and diarrhea were the most common adverse events reported across studies. The studies examined in this review suggest that RAM plus FOLFIRI or irinotecan have activity in previously treated GEA irrespective of prior-taxane use. Overall, RAM plus FOLFIRI or irinotecan was well tolerated with no new safety concerns identified beyond established profiles for these regimens.